PECULIARITIES OF ANTENATAL AND POSTNATAL PERIODS OF CHILD DEVELOPMENT WITH INFLAMMATORY MAXILLOFACILAL LOCALIZATION PROCESSES - Tkachenko, P.I.; Bilokon, S.O.; Lokhmatova, N.M.; Dolenko, O.B.; Popelo, Yu.V.; Korotych, N.M. (World of Medicine and Biology, 2020)
For the period of 7 years, 537 children with acute purulent odontogenic and non-odontogenic processes of maxillofacial area were examined. Acute purulent lymphadenitis (29 %) and adenoflegmon and odontogenic osteomyelitis, which accounted for 18 %, were found to be predominant in their structure. Noteworthy is the fact that a large number of children and their relatives seek specialized care behind time and are often treated for the wrong diagnosis. There are also certain age differences depending on the nosological form of the disease. Analysis of pregnancy showed that in this period, in the examined children’s mothers cases of acute infectious diseases, the presence of pathological conditions were quite frequently observed, and this has reflected in childbirth. It is also noteworthy that infants who were in artificial and mixed feeding from the age of one month and six months were more likely to fall ill. This situation indicates the need to include these children to the risk group in order to timely recover, which can negate the impact of adverse factors that they have experienced in both the ante- and post-natal periods of their development.
Keywords: children; developmental periods; lymphadenitis; adenophlegmon; osteomyelitis